Total Quality Management in an Automobile Supply Chain in Indian Market – A Case Study on Maruti Suzuki - Akshaya Kumar Sahoo (International Journal of Supply Chain Management, 2013)
In Indian market, customers see the quality ofthe product and simultaneously the price of that product. So, to be a winner inIndian market, quality of the product plays a major role with a peep into thedifferent segmented customers. So, total quality management (TQM) has beenwidely accepted as the ways and means for maintaining supply chain quality.From design to manufacturing, from factory to retailers or dealers or to endcustomers business are accepting TQM approach for achieving quality excellencethroughout the supply chain management. Hence, it is an attempt to describe howTQM is implemented for achieving supply chain quality management to influenceIndian market. Maruti Suzuki has taken as the best example for this context.